On 3d theory of acoustic metamaterials with a triple-periodic system of interior obstacles - M. Yu. Remizov; M. A. Sumbatyan (National Academy of Sciences of Armenia)
In a three-dimensional (3-D) context an analytical approach is proposed to study the propagation of elastic plane wave through a system of any finite number of parallel doubly-periodic identical gratings of coplanar cracks. In the low frequency range the problem is reduced to a system of integral equations holding over the crack of a chosen elementary rectangular cell of the grating. The semi-analytical method previously introduced for scalar and elastic 2-D problems gives an explicit representations for the wave field and the scattering parameters - the reflection and transmission coefficients.В трёхмерной постановке предлагается аналитический метод исследования распространения плоской упругой волны через систему произвольного конечного числа параллельных двоякопериодических идентичных массивов трещин. В условиях низкочастотного режима задача сводится к системе интегральных уравнений на одной выделенной типовой прямоугольной трещине. Полуаналитический метод, разработанный ранее для трёхмерных скалярных и плоских упругих задач, приводит к явным аналитическим представлениям для волнового поля и параметров рассеяния - коэффициентов отражения и прохождения. Եռաչափ դրվածքով առաջարկվում է ճաքերի կամայական վերջավոր թվով զուգահեռ երկպարբերական նույնական զանգվածներով հարթ առաձգական ալիքի տարածման հետազոտման վերլուծական եղանակ: Ցածր հաճախականության ռեժիմի պայմաններում խնդիրը բերվում է մեկ առանձնացված տիպային ուղղանկյունային ճաքի վրա ինտեգրալ հավասարումների համակարգի: Եռաչափ սկալյար և առաձգական հարթ խնդիրների համար նախկինում մշակված կիսավերլուծական եղանակը բերում է բացահայտ անալիտիկ արտահայտությունների ալիքային դաշտի և ցրման պարամետրերի՝ արտացոլման և անցման գործակիցների, համար:
Keywords: Mechanics of deformable solids; Waves